Pattern of decision making of urban land policies in the physical development (case study: SARI) - masoumeh amiribesheli; hosein mogtabazadekhanghahi; yosefali ziari; ali nourikermani (تحقیقات کاربردی علوم جغرافیایی)
The urban land management is an l part of the urban management. In some countries such as Iran, there is no integrated urban land management and providing municipal services is assigned to nationwide organisations. This means urban management is offered by the municipality or subsidiaries of the aforementioned organisations such dispersion has occurred during serval decades. It is considered as the roots of organizatinal inefficiencies ( offocial and financial corruption is regarded as basic reasin for many crimes) and the origin or many conflicts between people and organizations(judicial) To do so, it follows an applied analytical descriptive approach. To analyse the data, mathematical and statistical methods were applied using Excel and SPSS.  Moreover, the GIS was used for visualisation and adaptive analysis. The study concluded that lack of clear visions and consequently uncoordinated organisations and their policies, isolated and vertical decision-making, and unmanaged intervention without the required organisational capacities are the critical reasons for inefficient urban land management.